Rapid Detection of Imipenem Resistance in Gram-Negative Bacteria Using Tabletop Scanning Electron Microscopy: A Preliminary Evaluation - Haddad, Gabriel; Fontanini, Anthony; Bellali, Sara; Takakura, Tatsuki; Ominami, Yusuke; Hisada, Akiko; Hadjadj, Linda; Rolain, Jean-Marc; Raoult, Didier; Bou Khalil, Jacques Yaacoub (Frontiers in Microbiology, 2021)
Background: Enabling faster Antimicrobial Susceptibility Testing (AST) is critical, especially to detect antibiotic resistance, to provide rapid and appropriate therapy and to improve clinical outcomes. Although several standard and automated culture-based methods are available and widely used, these techniques take between 18 to 24 hours to provide robust results. Faster techniques are needed to reduce the delay between test and results. Methods: Here we present a high throughput AST method using a new generation of tabletop scanning electron microscope, to evaluate bacterial ultra-structural modifications associated with susceptibilities to imipenem as a proof of concept. A total of 71 reference and clinical strains of Gram-negative bacteria were used to evaluate susceptibility towards Imipenem after 30, 60 and 90 minutes of incubation. The length, width and electron density of bacteria were measured and compared between imipenem susceptible and resistant strains. Results: We correlated the presence of these morphological changes to the bacterial susceptibility and their absence to the bacterial resistance (e.g., Pseudomonas aeruginosa length without [2.24±0.61μm] and with [2.50±0.68μm] imipenem after 30 minutes [p=3.032E-15]; Escherichia coli width without [0.92±0.07μm] and with [1.28±0.19μm] imipenem after 60 minutes [p=1.242E-103]). We validated our method by a blind test on a series of 58 clinical isolates where all strains were correctly classified as susceptible or resistant towards imipenem. Conclusion: This method could be a potential tool in rapidly identifying carbapenem-resistance in Enterobacterales in clinical microbiology laboratories in less than two hours, allowing the empirical treatment of patients to be rapidly adjusted.